Strategi Implementasi Parenting Education dalam Meningkatkan Dukungan Orang Tua terhadap Kebijakan Disiplin Sekolah (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the implementation strategies of Parenting Education in enhancing parental support for elementary school discipline policies through a Systematic Literature Review (SLR) approach. The review focuses on mapping the forms of parenting strategies, patterns of implementation, and their impact on student disciplinary behavior. Data were obtained from eight national journal articles indexed in SINTA, published during the period 2020–2026, which were collected through Google Scholar with the help of the Publish or Perish application. Data analysis was conducted using thematic analysis through the stages of selection, reduction, grouping, and synthesis of research findings. The study results indicate that the dominant Parenting Education strategies include habituation, modeling, two-way communication, democratic parenting styles, and ongoing collaboration between schools and parents. The implementation of these strategies impacts the improvement of students' compliance with rules, learning responsibility, as well as consistency in disciplined behavior at both school and home. These findings affirm that Parenting Education is a strategic approach in strengthening the synergy between schools and families to support the successful and sustainable implementation of elementary school discipline policies